Fuzzy Logic Diagnostics for Open-Circuit Faults in Renewable Energy Voltage Source Inverters with Changeable Load Conditions - Dhumale, N. R.; Dhumale, R. B.; Shelke, M. V.; Nikam, S. S.; Mane, P. B.; Sarawade, A. N. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In this paper, a three-phase voltage source inverter (VSI) fault diagnosis system based on Fuzzy Logic is proposed. The Fuzzy Logic Fault Diagnosis (FLFD) system consists of four main stages such as PVM-Current Normalizer and Typical Transient Suppressor, Discrete Wavelet Transform, Feature Selection and Fuzzy Logic (FL). The crucial prerequisites for the aforementioned steps, including feature selection, mother wavelet selection, and FL structure, are covered in detail. The time domain waveform is used to clarify the terms PVM-current normalizer and typical transient suppressor. Due to the employment of a PVM-current normalizer and a conventional transient suppressor, this system is less dependent on mechanical or electrical operating conditions than other fault diagnostic methods. The choice of the mother wavelet and the level of decomposition are described in detail. By using the fewest possible features, the FLFD system identifies a variety of potential faults under varied load and different frequency. The approach for selecting features that work well is described. To categories faults, a FL’s architecture is built. On a suitable dataset, the system is implemented, and its performance is assessed. The experimental findings demonstrate the suggested system’s superior performance and ability to accurately diagnose VSI issues.